# The value of \[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\] is_________.

Answer

Verified

364.5k+ views

Hint: You can solve this problem by taking logarithm and after that you will come to know that you have to use L-Hospital’s Rule

Step by step solution:

We will rewrite the given equation first,

\[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

Consider it as L,

\[\therefore L=\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

We will put limits directly,

\[\therefore L={{\left( \dfrac{{{20}^{\infty }}-1}{19({{5}^{\infty }})} \right)}^{\dfrac{1}{\infty }}}\]

\[\therefore L={{\left( \dfrac{\infty }{\infty } \right)}^{0}}\]

As it is an indeterminate form therefore we should solve it by using different method,

\[\therefore L=\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

Taking log on both sides, we will get

\[\therefore \log L=\log \left[ \underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}} \right]\]

As we all know that ‘log’ can be inserted in limits,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \log {{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}} \right]\]

To proceed further we should know some rules of logarithm which are given below,

Formulae:

1.\[\log ({{m}^{n}})=n\times \log m\]

2.\[\log \left( \dfrac{m}{n} \right)=\log m-\log n\]

3.\[\log \left( m\times n \right)=\log m+\log n\]

By using formula 1 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{1}{x}\times \log \left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right) \right]\]

By using formula 2 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\log \left( 19\times {{5}^{x}} \right) \right]\]

By using formula 3 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\left[ \log 19+\log {{5}^{x}} \right] \right]\]

By using formula 1 again we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\left[ \log 19+x\times \log 5 \right] \right]\]

Now we will give negative sign inside the bracket,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\left[ \log \left( {{20}^{x}}-1 \right)-\log 19-x\times \log 5 \right]}{x}\]

We will divide each term by x which is in the denominator to simplify the expression,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\dfrac{\log 19}{x}-\dfrac{x\times \log 5}{x} \right]\]

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\dfrac{\log 19}{x}-\log 5 \right]\]

As we all know limits can be given separately for each term, therefore we can write above equation as,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\log 5\]

If we put the limits in the last term it won’t change as it’s a constant therefore, it can be written as,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\log 5\]………………………………………………. (a)

(i) (ii)

We should solve (i) and (ii) separately,

Consider,

\[L1=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}\]

If we put limits directly we will get,

\[\therefore L1=\dfrac{\log \left( {{20}^{\infty }}-1 \right)}{\infty }\]

\[\therefore L1=\dfrac{\infty }{\infty }\]

As it is giving a \[\dfrac{\infty }{\infty }\] form which is an indeterminate form therefore we should L-Hospital’s Rule which is given below,

L-Hospital’s Rule:

If a limit of a function is giving an indeterminate form then,

\[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f(x)}{g(x)}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{\dfrac{d}{dx}f(x)}{\dfrac{d}{dx}g(x)}\],

And we can take the derivatives till the denominator is not becoming zero if we put the limits.

By using L-Hospital’s Rule we can write L1 as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\dfrac{d}{dx}\left[ \log \left( {{20}^{x}}-1 \right) \right]}{\dfrac{d}{dx}\left( x \right)} \right]\]

Before proceeding further we should know the formulae of derivatives given below,

Formulae:

4. \[\dfrac{d}{dx}\left( \log x \right)=\dfrac{1}{x}\]

5. \[\dfrac{d}{dx}\left( {{a}^{x}} \right)={{a}^{x}}\times \log a\]

6. \[\dfrac{d}{dx}\left( x \right)=1\]

By using formula 4 and 6 we can write L1 as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\dfrac{1}{\left( {{20}^{x}}-1 \right)}\times \dfrac{d}{dx}\left( {{20}^{x}}-1 \right)}{1} \right]\]

By using formula 5 we can write above equation as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{1}{\left( {{20}^{x}}-1 \right)}\times {{20}^{x}}\times \log 20 \right]\]

As we observe above equation we can easily see that the denominator is still not vanished and still

maintaining the \[\dfrac{\infty }{\infty }\] form so we have to use L-Hospitals rule again. But it will be

lengthy as solved above.

To solve it shortly and to save time we can just take \[{{20}^{x}}\]common from denominator, therefore

we can write above equation as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{{{20}^{x}}\times \log 20}{{{20}^{x}}\left( 1-\dfrac{1}{{{20}^{x}}} \right)} \right]\]

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log 20}{\left( 1-\dfrac{1}{{{20}^{x}}} \right)} \right]\]

Now put the limits directly to get the answer,

\[\therefore L1=\dfrac{\log 20}{\left( 1-\dfrac{1}{{{20}^{\infty }}} \right)}\]

\[\therefore L1=\dfrac{\log 20}{\left( 1-\dfrac{1}{\infty } \right)}\]

As we all know that the value of \[\dfrac{1}{\infty }\] is 0,

\[\therefore L1=\dfrac{\log 20}{\left( 1-0 \right)}\]

\[\therefore L1=\log 20\]……………………………………………………………….. (b)

Consider,

\[L2=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}\]

If we put the limits directly we will get,

\[\therefore L2=\dfrac{\log 19}{\infty }\]

As we all know that the value of \[\dfrac{1}{\infty }\] is 0, therefore above equation will become,

\[\therefore L2=0\times \log 19\]

\[\therefore L2=0\]………………………………………………………………….. (c)

Now put the value of equation (b) and (c) in equation (a) we will get,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\log 5\]

\[\therefore \log L=\log 20-0-\log 5\]

\[\therefore \log L=\log 20-\log 5\]

If we use the formula 2 in above equation we will get,

\[\therefore \log L=\log \dfrac{20}{5}\]

\[\therefore \log L=\log 4\]

We will take antilog on both sides to get the final answer,

\[\therefore L=4\]

\[\therefore \underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}=4\]

Therefore the value of \[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\] is 4.

Note: You can commit a mistake which I have shown below, but do remember that x is tending to infinity

and not tending to Zero and therefore the formula is not applicable in the above case.

\[\underset{x\to 0}{\mathop{\lim }}\,{{\left( {{a}^{x}}-1 \right)}^{\dfrac{1}{x}}}=e\] but \[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( {{20}^{x}}-1 \right)}^{\dfrac{1}{x}}}\ne e\]

Step by step solution:

We will rewrite the given equation first,

\[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

Consider it as L,

\[\therefore L=\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

We will put limits directly,

\[\therefore L={{\left( \dfrac{{{20}^{\infty }}-1}{19({{5}^{\infty }})} \right)}^{\dfrac{1}{\infty }}}\]

\[\therefore L={{\left( \dfrac{\infty }{\infty } \right)}^{0}}\]

As it is an indeterminate form therefore we should solve it by using different method,

\[\therefore L=\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\]

Taking log on both sides, we will get

\[\therefore \log L=\log \left[ \underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}} \right]\]

As we all know that ‘log’ can be inserted in limits,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \log {{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}} \right]\]

To proceed further we should know some rules of logarithm which are given below,

Formulae:

1.\[\log ({{m}^{n}})=n\times \log m\]

2.\[\log \left( \dfrac{m}{n} \right)=\log m-\log n\]

3.\[\log \left( m\times n \right)=\log m+\log n\]

By using formula 1 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{1}{x}\times \log \left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right) \right]\]

By using formula 2 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\log \left( 19\times {{5}^{x}} \right) \right]\]

By using formula 3 we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\left[ \log 19+\log {{5}^{x}} \right] \right]\]

By using formula 1 again we can write log L as shown below,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{1}{x}\times \left[ \log \left( {{20}^{x}}-1 \right)-\left[ \log 19+x\times \log 5 \right] \right]\]

Now we will give negative sign inside the bracket,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\left[ \log \left( {{20}^{x}}-1 \right)-\log 19-x\times \log 5 \right]}{x}\]

We will divide each term by x which is in the denominator to simplify the expression,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\dfrac{\log 19}{x}-\dfrac{x\times \log 5}{x} \right]\]

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\dfrac{\log 19}{x}-\log 5 \right]\]

As we all know limits can be given separately for each term, therefore we can write above equation as,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\log 5\]

If we put the limits in the last term it won’t change as it’s a constant therefore, it can be written as,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\log 5\]………………………………………………. (a)

(i) (ii)

We should solve (i) and (ii) separately,

Consider,

\[L1=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}\]

If we put limits directly we will get,

\[\therefore L1=\dfrac{\log \left( {{20}^{\infty }}-1 \right)}{\infty }\]

\[\therefore L1=\dfrac{\infty }{\infty }\]

As it is giving a \[\dfrac{\infty }{\infty }\] form which is an indeterminate form therefore we should L-Hospital’s Rule which is given below,

L-Hospital’s Rule:

If a limit of a function is giving an indeterminate form then,

\[\underset{x\to a}{\mathop{\lim }}\,\dfrac{f(x)}{g(x)}=\underset{x\to a}{\mathop{\lim }}\,\dfrac{\dfrac{d}{dx}f(x)}{\dfrac{d}{dx}g(x)}\],

And we can take the derivatives till the denominator is not becoming zero if we put the limits.

By using L-Hospital’s Rule we can write L1 as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\dfrac{d}{dx}\left[ \log \left( {{20}^{x}}-1 \right) \right]}{\dfrac{d}{dx}\left( x \right)} \right]\]

Before proceeding further we should know the formulae of derivatives given below,

Formulae:

4. \[\dfrac{d}{dx}\left( \log x \right)=\dfrac{1}{x}\]

5. \[\dfrac{d}{dx}\left( {{a}^{x}} \right)={{a}^{x}}\times \log a\]

6. \[\dfrac{d}{dx}\left( x \right)=1\]

By using formula 4 and 6 we can write L1 as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\dfrac{1}{\left( {{20}^{x}}-1 \right)}\times \dfrac{d}{dx}\left( {{20}^{x}}-1 \right)}{1} \right]\]

By using formula 5 we can write above equation as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{1}{\left( {{20}^{x}}-1 \right)}\times {{20}^{x}}\times \log 20 \right]\]

As we observe above equation we can easily see that the denominator is still not vanished and still

maintaining the \[\dfrac{\infty }{\infty }\] form so we have to use L-Hospitals rule again. But it will be

lengthy as solved above.

To solve it shortly and to save time we can just take \[{{20}^{x}}\]common from denominator, therefore

we can write above equation as,

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{{{20}^{x}}\times \log 20}{{{20}^{x}}\left( 1-\dfrac{1}{{{20}^{x}}} \right)} \right]\]

\[\therefore L1=\underset{x\to \infty }{\mathop{\lim }}\,\left[ \dfrac{\log 20}{\left( 1-\dfrac{1}{{{20}^{x}}} \right)} \right]\]

Now put the limits directly to get the answer,

\[\therefore L1=\dfrac{\log 20}{\left( 1-\dfrac{1}{{{20}^{\infty }}} \right)}\]

\[\therefore L1=\dfrac{\log 20}{\left( 1-\dfrac{1}{\infty } \right)}\]

As we all know that the value of \[\dfrac{1}{\infty }\] is 0,

\[\therefore L1=\dfrac{\log 20}{\left( 1-0 \right)}\]

\[\therefore L1=\log 20\]……………………………………………………………….. (b)

Consider,

\[L2=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}\]

If we put the limits directly we will get,

\[\therefore L2=\dfrac{\log 19}{\infty }\]

As we all know that the value of \[\dfrac{1}{\infty }\] is 0, therefore above equation will become,

\[\therefore L2=0\times \log 19\]

\[\therefore L2=0\]………………………………………………………………….. (c)

Now put the value of equation (b) and (c) in equation (a) we will get,

\[\therefore \log L=\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log \left( {{20}^{x}}-1 \right)}{x}-\underset{x\to \infty }{\mathop{\lim }}\,\dfrac{\log 19}{x}-\log 5\]

\[\therefore \log L=\log 20-0-\log 5\]

\[\therefore \log L=\log 20-\log 5\]

If we use the formula 2 in above equation we will get,

\[\therefore \log L=\log \dfrac{20}{5}\]

\[\therefore \log L=\log 4\]

We will take antilog on both sides to get the final answer,

\[\therefore L=4\]

\[\therefore \underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}=4\]

Therefore the value of \[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( \dfrac{{{20}^{x}}-1}{19({{5}^{x}})} \right)}^{\dfrac{1}{x}}}\] is 4.

Note: You can commit a mistake which I have shown below, but do remember that x is tending to infinity

and not tending to Zero and therefore the formula is not applicable in the above case.

\[\underset{x\to 0}{\mathop{\lim }}\,{{\left( {{a}^{x}}-1 \right)}^{\dfrac{1}{x}}}=e\] but \[\underset{x\to \infty }{\mathop{\lim }}\,{{\left( {{20}^{x}}-1 \right)}^{\dfrac{1}{x}}}\ne e\]

Last updated date: 26th Sep 2023

•

Total views: 364.5k

•

Views today: 10.64k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

The poet says Beauty is heard in Can you hear beauty class 6 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the past tense of read class 10 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE